Muscle Characteristics in Pediatric Hereditary Spastic Paraplegia vs. Bilateral Spastic Cerebral Palsy: An Exploratory Study - De Beukelaer, Nathalie; Bar-On, Lynn; Hanssen, Britta; Peeters, Nicky; Prinsen, Sandra; Ortibus, Els; Desloovere, Kaat; Van Campenhout, Anja (Frontiers in Neurology, 2021)
Hereditary spastic paraplegia (HSP) is a neurological, genetic disorder that predominantly presents with lower limb spasticity and muscle weakness. Pediatric pure HSP types with infancy or childhood symptom onset resemble in clinical presentation to children with bilateral spastic cerebral palsy (SCP). Hence, treatment approaches in these patient groups are analogous. Altered muscle characteristics, including reduced medial gastrocnemius (MG) muscle growth and hyperreflexia have been quantified in children with SCP, using 3D-freehand ultrasound (3DfUS) and instrumented assessments of hyperreflexia, respectively. However, these muscle data have not yet been studied in children with HSP. Therefore, we aimed to describe these MG muscle characteristics in HSP and to test the hypothesis that these data differ from those of children with SCP and typically developing (TD) children. A total of 41 children were enrolled including (1) 9 children with HSP (ages of 9 to 17 years with gross motor function levels I and II), (2) 17 age-and severity-matched SCP children and (3) 15 age-matched typical developing children (TD). Clinically, children with HSP showed significantly increased presence and severity of ankle clonus compared to SCP (p=0.009). Compared to TD, both HSP and SCP had significantly smaller MG muscle volume normalized to body mass (p=0.001). Hyperreflexia did not significantly differ between the HSP and SCP group. In addition to the observed pathological muscle activity for both the low-velocity and the change in high-velocity and low-velocity stretches in the two groups, children with HSP tended to present higher muscle activity in response to increased stretch velocity compared to SCP. This study is the first to reveal MG muscle volume deficits in children with HSP. Moreover, high-velocity-dependent hyperreflexia and ankle clonus is observed in children with HSP. Instrumented impairment assessments confirmed similar altered MG muscle characteristics in pure HSP type with pediatric onset compared to bilateral SCP. Hence, the study results indicate analogous treatment approaches in these two patient groups.